The positional technical and running performance of sub-elite Gaelic football. Issue 3 (2nd July 2020) - Mangan, Shane; Collins, Kieran; Burns, Con; O'Neill, Cian
ABSTRACT: Introduction: The current research examines the positional technical and running performance of sub-elite Gaelic football match-play and compares technical and running performance between Division 1 and Division 2 teams. Methods: Sixty eight sub-elite Gaelic football players from two teams were monitored via global positioning system (GPS) microtechnology (GPEXE LT 18 Hz, Exelio, Udine, Italy) and a video camera across 30 competitive matches (n = 336). Comparisons between teams and playing positions were examined for selected technical and running performance variables. Results: Playing position had large effects on several variables including number of possessions (ES = 0.18), number of shots (ES = 0.45), total m per minute (ES = 0.403), average speed (ES = 0.40), number of power events (ES = 0.3) and recovery time between power events (ES = 0.31). Playing standard had trivial to small effects on all technical performance variables (ES ≤ 0.47) and trivial to small effects (ES ≤ 0.48) on all running performance variables. Conclusion: The current study demonstrates that there are distinct positional demands in sub-elite Gaelic football. The findings of this research also demonstrate that there is little difference in the technical and running performance of Division 1 and Division 2 sub-elite teams.